COGNITIVE LOAD THEORY AND THE USE OF WORKED EXAMPLES AS AN INSTRUCTIONAL STRATEGY IN PHYSICS FOR DISTANCE LEARNERS: A PRELIMINARY STUDY - Saw, Kim Guan (Anadolu University, 2017)
This article revisits the cognitive load theory to explore the use of worked examples to teach a selected topic in a higher level undergraduate physics course for distance learners at the School of Distance Education, Universiti Sains Malaysia. With a break of several years from receiving formal education and having only minimum science background, distance learners need an appropriate instructional strategy for courses that require complex conceptualization and mathematical manipulations. As the working memory is limited, distance learners need to acquire domain specific knowledge in stages to lessen cognitive load. This article charts a learning task with a lower cognitive load to teach Fermi-Dirac distribution and demonstrates the use of sequential worked examples. Content taught in stages using worked examples can be presented as a form of didactic conversation to reduce transactional distance. This instructional strategy can be applied to similar challenging topics in other well-structured domains in a distance learning environment.